STUDI REAKSI SIKLOPENTILSILAN DENGAN 4-IODIDA THIOANISOL MENGGUNAKAN KATALIS PALADIUM - Lesbani, Aldes; Mohadi, Risfidian; Elfita, Elfita (Jurnal Kimia (Journal of Chemistry), 2013)
A study on cyclopentylsilane reaction in tetrahydrofuran with 4-iodo thioanisol has been carried out using palladium as catalyst under argon atmosphere at room temperature. The results showed that the product was tris(4-thioanisyl)cyclopentylsilane (1) which was obtained from recrystallization using methanol with the yield 35%. The Compound (1) has a melting point of 91.5-92.0 o C. Analysis using GC-MS found m / z 466 with six equivalent protons and eight carbons peak obtained from 1 H and 13 C NMR.
Keywords: cyclopentylsilane, 4-iodo thioanisol, palladium